2017
DOI: 10.1002/hep4.1111
|View full text |Cite
|
Sign up to set email alerts
|

Generation of safe and therapeutically effective human induced pluripotent stem cell‐derived hepatocyte‐like cells for regenerative medicine

Abstract: Hepatocyte‐like cells (HLCs) differentiated from human induced pluripotent stem (iPS) cells are expected to be applied for regenerative medicine. In this study, we attempted to generate safe and therapeutically effective human iPS‐HLCs for hepatocyte transplantation. First, human iPS‐HLCs were generated from a human leukocyte antigen‐homozygous donor on the assumption that the allogenic transplantation might be carried out. Highly efficient hepatocyte differentiation was performed under a feeder‐free condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Recent studies described the production of transplantable HLCs using GMP‐compatible hepatic differentiation protocol, but culture times were about 30 days vs 11 days for pHSCs. Takayama et al demonstrated a very efficient cryopreservation of HLCs using a GMP‐compatible cryopreservation solution, but cells functionality was not confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies described the production of transplantable HLCs using GMP‐compatible hepatic differentiation protocol, but culture times were about 30 days vs 11 days for pHSCs. Takayama et al demonstrated a very efficient cryopreservation of HLCs using a GMP‐compatible cryopreservation solution, but cells functionality was not confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies described the production of transplantable HLCs using GMP‐compatible hepatic differentiation protocol, but culture times were about 30 days vs 11 days for pHSCs. Takayama et al demonstrated a very efficient cryopreservation of HLCs using a GMP‐compatible cryopreservation solution, but cells functionality was not confirmed in vivo. While our study did not allow to compare pHSCs efficiency with the one of HLCs, our data show that pHSCs can efficiently be transplanted in Gunn rats to correct hyperbilirubinemia, using a protocol asking two times less time, and in absence of liver pre‐conditioning that would give a selective growth advantage to transplanted hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that human iPS cells differentiate into hepatocyte or cholangiocyte lineages in vitro [4][5][6][7][8]. Hepatocyte-like cells derived from iPS cells (iPS-Heps) exhibit properties of hepatocytes, such as albumin secretion and metabolic functional properties.…”
Section: Diseases Models Of Genetic Liver Diseasesmentioning
confidence: 99%
“…Human induced pluripotent stem (iPS) cells are somatic cells genetically reprogrammed to be pluripotent by the transient expression of genes essential for maintaining the properties of embryonic stem cells [3]. Human iPS and human embryonic stem cells exhibit the potential for differentiation into various cell types, including hepatic lineages [4][5][6][7][8]. Such pluripotent stem cells are candidates for regenerative medicine and a promising tool to evaluate the pathophysiology of genetic or non-genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Human pluripotent stem cells are useful as a model of liver development because they differentiate into hepatocytes by mimicking early liver development. We optimized the growth factors and small molecular compounds added in hepatic differentiation and succeeded in developing an efficient hepatic differentiation protocol of human induced pluripotent stem (iPS) cells . In addition, we searched for genes and compounds that can improve the homologous recombination efficiency of human iPS cells using the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)‐Cas9 system.…”
mentioning
confidence: 99%